2013
DOI: 10.3354/meps10222
|View full text |Cite
|
Sign up to set email alerts
|

High-use areas, seasonal movements and dive patterns of juvenile loggerhead sea turtles in the Southwestern Atlantic Ocean

Abstract: Characterizing the behaviors of sea turtles and identifying high-use areas as they vary in time and space is important for conservation planning, particularly when turtles overlap with fisheries that may unintentionally harm them. Between July 2006 and March 2010, 27 satellite transmitters were deployed at sea on juvenile loggerheads Caretta caretta captured as bycatch in the Uruguayan and Brazilian pelagic longline fisheries operating in the Southwestern Atlantic Ocean. Tracking duration ranged from 3 to 639 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 61 publications
0
18
0
1
Order By: Relevance
“…It is important to note that drifters are constrained to the surface, whereas turtles are not, an important caveat noted by other studies [15]. Analysis of the pressure recording tags affixed to a subset of 5 turtles revealed that when the turtles were below the surface, they attained a maximum depth between 10 and 100 m 84% of the time (see [16] for a summary of dive depths for these turtles), suggesting that when diving, turtles often occupy the zone near where the drifters are drogued. Even in light of the differences in drifter configuration and turtle behavior, the comparison of the passive advection of drifters to the movement of turtles has yielded valuable insight into the active movement and foraging behavior of turtles ( e .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is important to note that drifters are constrained to the surface, whereas turtles are not, an important caveat noted by other studies [15]. Analysis of the pressure recording tags affixed to a subset of 5 turtles revealed that when the turtles were below the surface, they attained a maximum depth between 10 and 100 m 84% of the time (see [16] for a summary of dive depths for these turtles), suggesting that when diving, turtles often occupy the zone near where the drifters are drogued. Even in light of the differences in drifter configuration and turtle behavior, the comparison of the passive advection of drifters to the movement of turtles has yielded valuable insight into the active movement and foraging behavior of turtles ( e .…”
Section: Resultsmentioning
confidence: 99%
“…Scientific observers of PNOFA-DINARA (the Uruguayan National Program of Scientific Observers Onboard the Tuna Fleet) [16, 17] and Projeto TAMAR-ICMBio (the national Brazilian sea turtle conservation program) [18] deployed satellite transmitters on loggerhead sea turtles incidentally captured in Brazilian and Uruguayan pelagic long-line fisheries operating in the southwestern Atlantic Ocean between July of 2006 and November of 2009. The turtle trajectories used in this study span a 5-year period between July 2006 and December 2011(Fig 1E) and are available in S1 File.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The proximity of nesting beaches may help explain the high rate of subadult/adult bycatch of this species in the study area, as previously suggested by Guimarães et al (). In addition, C. caretta subadults and adults prefer neritic habits, foraging near the bottom (Barceló et al, ; Monteiro, ), where this fishery operates. The large volume of bycatch discarded by trawls may also attract sea turtles (Beneditto, Moura, & Siciliano, ; Tomas, Aznar, & Raga, ), creating a high density of turtles in areas being actively fished, thereby increasing the rates of turtle bycatch (Shoop & Ruckdeschel, ).…”
Section: Discussionmentioning
confidence: 99%